1998
DOI: 10.1038/ng0198-69
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the regulatory region of APOE associated with risk for Alzheimer's dementia

Abstract: The epsilon4 allele of the apolipoprotein E gene (APOE) has been associated with an increased risk of developing Alzheimer's disease (AD; refs 1,2). However, it is apparent that the APOEepsilon4 allele alone is neither necessary nor sufficient to cause the disease. We have recently found three new polymorphisms within the APOE transcriptional regulatory region (M.J.A. et al., manuscript submitted) and now establish an association between one of these polymorphisms (-491A/T) and dementia as observed in Alzheime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
4
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(192 citation statements)
references
References 18 publications
11
174
4
3
Order By: Relevance
“…It should be emphasised that no attempt to correct for multiple testing was made in other studies. 4,6,7 In order to circumvent the problem posed by correction for multiple testing (which could lead to false negative results), we then analysed the three promoter polymorphisms as a single haplotyped marker with three alleles. Thus the number of tests was reduced and the study had more power to detect a possible role of the APOE promoter.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasised that no attempt to correct for multiple testing was made in other studies. 4,6,7 In order to circumvent the problem posed by correction for multiple testing (which could lead to false negative results), we then analysed the three promoter polymorphisms as a single haplotyped marker with three alleles. Thus the number of tests was reduced and the study had more power to detect a possible role of the APOE promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies suggested that genetic variability in the regulatory region of APOE could modulate the risk associated with the APOEε4 isoform. In population-based studies, genetic association with AD, independent of APOEε4, was reported for three APOE promoter variations (-491A/T, -427T/C, and -219T/G) [124,125,126]. Functional analysis showed that these polymorphisms alter the transcriptional activity of the APOE promoter due to differential binding of transcription factors.…”
Section: Susceptibility Genes For Eoadmentioning
confidence: 99%
“…Since ibuprofen treatment reduced GFAP in our APP trangenics (Lim et al, 2000), we reasoned that control of inflammation and gliosis might reduce apoE production. Although some reports show an association between increased apoE mRNA (or promoter polymorphisms promoting such increases) and AD risk or amyloid plaques (Diedrich et al, 1991;Yamada et al, 1995;Bullido et al, 1998;Lambert et al, 1998;Laws et al, 1999), other reports show that this relation is restricted to apoE4 cases (Lambert et al, 1997;Roks et al, 1998;Song et al, 1998;Pahnke et al, 2003).…”
Section: Introductionmentioning
confidence: 99%